Pelatihan Pembelajaran Jarak Jauh dalam di Masa Adaptasi Kebiasaan Baru (AKB) di SMPN 1 Banyuresmi Garut - Siti Nurkamilah; Rifaatul Muthmainah; Diah Ika Putri; Sri Wahjuningsih; Asep Rohayat (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2020)
This community service activity aims to improve teacher competence in distance learning during the adaptation period of new habits through the creation of online learning media, in particular making online questions based on google classrooms and interesting quizzes that can be easily used by teachers and students at SMPN 1 Banyuresmi. The service activity consists of two stages, the first stage is the delivery of material and the second stage is the practice of making online questions. The activity was attended by all teachers of SMPN 1 Banyuresmi. The training material is making online questions based on google classroom and quizziz. The results of the activity showed that community service was going well and smoothly. This was marked by a good response from the training participants and enthusiasm during the training and the application of online question making through the classroom and quizziz applications. the good is the point of view of assessment in this community service. Through this training, universities carry out their role to contribute to improving the competence of teachers or educators, especially in making learning media and online questions in Distance Learning activities. The obstacles that arise at this training stage are the relatively short time allocation, so that not all teachers can complete online question making